Pelatihan Kriya Anyaman: Inovasi Aksesoris Untuk Keterampilan Masyarakat - Mesi Herawati; Kholilatul Khusni; Yeyen Novita; Darma Taujiharrahman; Achmand Nur Alfianto; M. Bastomi Fahri Zusak (Jurnal Inovasi dan Pengabdian, 2026)
This community service activity aims to improve the skills and creativity of women in Neighborhood Association (RW) 30, Batursari Village, Mranggen District, Demak Regency, through weaving craft training in the production of creative accessories with both utility and economic value. The community faces a limited innovative skill set in developing woven products, resulting in a lack of variety and low competitiveness. The activity implemented a participatory approach and hands-on practice (learning by doing) through preparation, implementation, and evaluation. The activity included providing materials, demonstrating basic weaving techniques, and hands-on product-making practice with guidance from the community service team and woven craft MSMEs. The results demonstrated improved participant skills in creating various woven accessories such as key chains, tissue holders, and more. Furthermore, participants were able to combine various colors and product designs. Thus, this community service activity has a positive impact in supporting community economic empowerment through the development of innovative and marketable weaving craft skills.